Práctica tutelada en la formación de profesores de Química: análisis de la producción científica de Tesis y Disertaciones (2018-2022) - Jesus, Gilmara Barbosa de (2023)
In this article we question how the theme of curricular internship in the training of Chemistry teachers has been contemplated and discussed in Brazilian theses and dissertations focusing on internship as a field of research. The objective is to know the panorama of studies on the theme of curricular internships in chemistry teacher training courses, in order to identify how the research axis is characterized. It is also envisaged to analyze new perspectives for the supervised internship. This is a qualitative research, carried out from a Systematic Literature Review, which sought research in the Catalog of Theses and Dissertations of CAPES. We used the descriptors “Teacher Training”, “Supervised Internship” and “Chemistry Teaching” and found a total sum of 60 researches. After the selection and time frame, we considered 09 works as the final sample of the review, for analysis through Discursive Textual Analysis (DTA) due to the effectiveness and proximity of the contemplated theme. The internship has been contemplated as an articulation of theory and practice, propagated as a moment of approximation with the teaching profession. Some categories emerged during the analysis, we consider research in the internship context as a tendency and growing perspective in the formation of Chemistry teachers.